2018
DOI: 10.1590/1809-2950/16765225022018
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and use of the ICF in clinical practice by physiotherapists and occupational therapists of Minas Gerais

Abstract: This study aims to evaluate the profile and knowledge of physiotherapists and occupational therapists from Minas Gerais about the International Classification of Functioning, Disability and Health (ICF) application in professional practice, trying to understand the reason for the underutilization of this universal instrument in Brazil. Observational and cross-sectional study was conducted using an online questionnaire prepared by specialists. An email was sent to all physiotherapists and occupational therapist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
0
5
0
3
Order By: Relevance
“…The main challenge might be that it is mostly considered as an assessment instrument (Leonardi et al, 2005), mainly for clinical practice. Pernambuco et al (2018) observed that 82% of users believe that the ICF is only clinically applicable. The ICF's holistic approach (overcoming a mere deficit-symptom orientation) leads to a joint assessment of life areas without problems, but also of restrictions in participation and to meaningful participation goals in interaction with relevant environments.…”
Section: Discussionmentioning
confidence: 99%
“…The main challenge might be that it is mostly considered as an assessment instrument (Leonardi et al, 2005), mainly for clinical practice. Pernambuco et al (2018) observed that 82% of users believe that the ICF is only clinically applicable. The ICF's holistic approach (overcoming a mere deficit-symptom orientation) leads to a joint assessment of life areas without problems, but also of restrictions in participation and to meaningful participation goals in interaction with relevant environments.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of the ICF is not yet so widespread in Brazil 20 , the WHO suggests its use to contemplate the evaluation of individuals -in this case, of the infants in an integral way -and facilitate communication among professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Yanılma olasılığı p<0,05 olarak alındı. Çalışma için prospektif güç analizi yapılmadığından, 1-β=0,05 alınarak, post-hoc güç analizi yapıldı ve çalışmanın post-hoc gücü % 85,5 olarak hesaplandı (10,11).…”
Section: İstatistiksel Analizunclassified